Fighting African capital flight: timelines for the adoption of common policies - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
This paper provides an exhaustive assessment of feasible horizons for policy harmonization against African capital flight. The empirical evidence is based on a methodological innovation on common policy initiatives and the results are premised on 15 fundamental characteristics of African capital flight based on income-levels, legal origins, natural resources, political stability and religious domination. Based on the findings, a genuine standard-setting timeframe is in the horizon of 6-13 years. Within the timeframe, common policies are feasible and could be enforced without distinction of nationality or locality in identified fundamental characteristics with full convergence.
Keywords: C50; E62; F34; O19; O55; 330; Econometric modeling; Big push; Capital flight; Debt relief; Africa